Computer technology of images geometric correction - Шедловська, Яна (SWorldJournal, 2020)
This work is devoted to remote sensing imagery geometric transformation. In this work a method of geometric transformation of an aerospace image based on GCPs and linear elements of the image was proposed. To distinguish linear elements automatically, the